2016
DOI: 10.1016/j.cardfail.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Outflow Cannula Malfunction of Left Ventricular Assist Devices (LVADs) With the Use of Doppler Echocardiography: New LVAD-Specific Reference Values for Contemporary Devices

Abstract: Background Echocardiographic assessment of left ventricular assist devices (LVADs) is used as a screening tool to evaluate the integrity and mechanics of the pump and circuit. We aimed to 1) establish the normal range and upper reference limit of peak velocity of the outflow cannula for the modern era of LVADs and 2) assess the clinical performance of the currently cited and newly proposed reference limits in patients with continuous-flow LVADs as a screening tool for cannula malfunction. Methods LVAD outflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…2 Reports suggest that adequate echocardiographic images of the outflow graft can be obtained in >90%. 3 However, our echocardiographic success rate was only 71%, and the pressure gradient estimated was significantly lower than by catheterization. Thus, additional testing must be considered if the clinical suspicion remains high.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2 Reports suggest that adequate echocardiographic images of the outflow graft can be obtained in >90%. 3 However, our echocardiographic success rate was only 71%, and the pressure gradient estimated was significantly lower than by catheterization. Thus, additional testing must be considered if the clinical suspicion remains high.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, the rapidity with which flow drops does not distinguish between inflow and outflow cannula problems as proposed elsewhere 2 . Reports suggest that adequate echocardiographic images of the outflow graft can be obtained in >90% 3 . However, our echocardiographic success rate was only 71%, and the pressure gradient estimated was significantly lower than by catheterization.…”
Section: Discussionmentioning
confidence: 68%
“…The 2015 American Society of Echocardiography 10 guidelines recommended screening for outflow graft obstruction for velocities greater than 2 m/s. Conversely, independent investigations have reported device specific doppler velocities with average velocities for Heartmate II were 1.86 ± 0.44 m/s and for Heartware 2.36 ± 0.53 m/s 11 …”
Section: Discussionmentioning
confidence: 90%
“…Although there are limited data for the use of multi-imaging modalities for the diagnosis of LVAD dysfunction, prior studies have shown that transthoracic Doppler echocardiography can be used as a screening method to assess for OGO ( 4 ). Moreover, transesophageal echocardiography is suitable in the overall assessment of LVADs and can provide information for device position, ventricular function, valvular structure and hemodynamics, thrombus, aortic root anatomy, and inflow and outflow graft angulation.…”
Section: Discussionmentioning
confidence: 99%